Epistemic Injustice in Healthcare : the potential for Hermeneutical Injustice within South Africa's Primary Healthcare System - Ruttkamp-Bloem, Emma (University of Pretoria, 2019)
Dissertation (MA)--University of Pretoria, 2018.